2007
DOI: 10.1158/0008-5472.can-06-3688
|View full text |Cite
|
Sign up to set email alerts
|

TSP50 Encodes a Testis-Specific Protease and Is Negatively Regulated by p53

Abstract: Earlier studies suggested that TSP50 is a testis-specific gene that encodes a protein, which is homologous to serine proteases but differs in that threonine replaces serine in its catalytic triad. Most importantly, it was abnormally reactivated in many breast cancer biopsies tested. While further investigating its biochemical and cell biological natures, we found that TSP50 exhibited enzyme activity and was located in the endoplasmic reticulum and cytosol membrane. During our studies to elucidate the regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 45 publications
2
40
1
Order By: Relevance
“…As the TSP50 gene, which was negatively regulated by p53, was available in our lab, we cotransfected pGL/TSP50P (pGL containing the TSP50 promoter) with pcDNA/P53, in parallel, into MCF7/WT and HEK293 cells. The results clearly showed that p53 downregulated the TSP50 promoter (Xu et al, 2007), whereas it upregulated the WTH3 promoter. Similar results were obtained when MCF7/AdrR and Hela cells were used as hosts (data not shown), which suggested that WTH3 was upregulated by the p53 gene in a celltype independent manner.…”
Section: Resultsmentioning
confidence: 92%
“…As the TSP50 gene, which was negatively regulated by p53, was available in our lab, we cotransfected pGL/TSP50P (pGL containing the TSP50 promoter) with pcDNA/P53, in parallel, into MCF7/WT and HEK293 cells. The results clearly showed that p53 downregulated the TSP50 promoter (Xu et al, 2007), whereas it upregulated the WTH3 promoter. Similar results were obtained when MCF7/AdrR and Hela cells were used as hosts (data not shown), which suggested that WTH3 was upregulated by the p53 gene in a celltype independent manner.…”
Section: Resultsmentioning
confidence: 92%
“…TSP50 is a testis-specific protease which is known to be a cancer testis antigen (47,59). The expression is regulated in part by methylation of the promoter (22), is negatively regulated by p53 (56), and is abnormally activated in a high proportion of breast cancers (59). The third gene, Gal3st1, which encodes CST, showed the greatest reduction in transcripts in BORIS Ϫ/Ϫ testis (Table 2).…”
Section: Targeted Disruption Of the Boris Genementioning
confidence: 99%
“…Although the physiologic function of TSP50 is not clarified, the characteristic of its expression makes it interesting as a potential target for cancer immunotherapy. Recent publications suggested that expression of TSP50 is regulated by CpG methylation of the promoter (35), similar to many other CTAs, and by various transcription factors including SP1, CCAAT/enhancer binding protein (C/EBP), and TP53 (36,37). However, none of these factors was shown to regulate expression of TSP50 in a physiological context, which make it unclear which factors are involved in vivo.…”
Section: Ctcfmentioning
confidence: 99%